2012
DOI: 10.1073/pnas.1217204109
|View full text |Cite
|
Sign up to set email alerts
|

Sprouty genes function in suppression of prostate tumorigenesis

Abstract: Expression of Sprouty genes is frequently decreased or absent in human prostate cancer, implicating them as suppressors of tumorigenesis. Here we show they function in prostate tumor suppression in the mouse. Concomitant inactivation of Spry1 and Spry2 in prostate epithelium causes ductal hyperplasia and low-grade prostatic intraepithelial neoplasia (PIN). However, when Spry1 and Spry2 loss-of-function occurs in the context of heterozygosity for a null allele of the tumor suppressor gene Pten, there is a strik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
(60 reference statements)
0
34
1
Order By: Relevance
“…These data are in agreement with two recent reports showing that deletion of Spry family members in the context of Pten happloinsuficiency accelerates prostate tumorigenesis. 51,52 During the last years, it is becoming evident that OIS poses a potent barrier to tumoral transformation in vivo. Thus, the expression of activated Ras, E2f3 or B-Raf oncogenes in mice induces cellular senescence in premalignant tumors of the lung, pancreas, mammary gland, pituitary gland and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with two recent reports showing that deletion of Spry family members in the context of Pten happloinsuficiency accelerates prostate tumorigenesis. 51,52 During the last years, it is becoming evident that OIS poses a potent barrier to tumoral transformation in vivo. Thus, the expression of activated Ras, E2f3 or B-Raf oncogenes in mice induces cellular senescence in premalignant tumors of the lung, pancreas, mammary gland, pituitary gland and melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic ablation of both Spry1 and Spry2 alleles, which are negative regulators of RTK signaling, leads to the expected increase in pERK levels, but no significant regulation of AKT signaling was observed in the prostate. This context induced frequent ductal hyperplasia, occasionally progressing into low-grade prostatic intraepithelial neoplasia (PIN) lesions (66). These lesions were previously shown to display markers of senescence (67).…”
Section: Models Emerging From Genetically Engineered Micementioning
confidence: 99%
“…22,[25][26][27][28][29] Some sprouty proteins can specifically inhibit the Ras/MAPK signaling pathway and regulate pivotal signaling pathways that are essential to cancer oncogenesis or neoplasia, including angiogenesis, cytokinesis, cell proliferation, invasion, and migration. 18,[20][21][22]24,26,31,32 We found that Spry2 expression level was significantly lower in tumors than in adjacent non-cancer tissue samples, supporting its role as a tumor suppressor in RCC. Additionally, we confirmed that the inhibition of miR-122 promoted the expression of Spry2, suggesting that miR-122 may be involved in regulating malignant biological activity.…”
Section: Discussionmentioning
confidence: 69%